Peran Perpustakaan Sekolah dalam Meningkatkan Literasi Membaca Siswa - Mumtazien, Ghilman; Syam, Abdi Mubarak (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the role of school libraries in improving reading literacy among students of Al-Ulum Terpadu. School libraries play an important role in education, not only as a provider of information sources, but also as a facilitator of reading literacy skills development. Qualitative descriptive method with case study approach was used to explore the contribution of school libraries in improving students' reading interest and ability. Data collection was conducted through observation, in-depth interviews with librarians and teachers, and questionnaires to students. The results of the study indicate that school libraries have a significant role in supporting reading literacy through various programs, such as fostering reading interest, providing relevant and quality book collections, and literacy activities integrated with the curriculum. The active participation of libraries in these activities has been shown to increase student engagement in reading activities. In addition, the findings of this study emphasize the importance of synergy between libraries, teachers, and parents in building a sustainable reading culture. This study suggests that school libraries continue to strengthen their role in creating a conducive learning environment and supporting the development of student literacy. It is hoped that collaborative steps involving various parties will further increase the effectiveness of libraries as centers of literacy and learning. The implications of this study emphasize the importance of the role of school libraries in improving students' reading literacy. Schools need to increase support for libraries through the provision of quality collections and sustainable literacy programs. Librarian training and collaboration with teachers and parents must be optimized to create a strong reading culture. Educational policies that encourage the use of libraries as literacy centers need to be strengthened, so that libraries can function optimally as agents of change in developing student literacy. Penelitian ini bertujuan untuk menganalisis peran perpustakaan sekolah dalam meningkatkan literasi membaca di kalangan siswa Al-Ulum Terpadu. Perpustakaan sekolah memainkan peran penting dalam pendidikan, tidak hanya sebagai penyedia sumber informasi, tetapi juga sebagai fasilitator pengembangan keterampilan literasi membaca. Metode deskriptif kualitatif dengan pendekatan studi kasus digunakan untuk mengeksplorasi kontribusi perpustakaan sekolah dalam meningkatkan minat dan kemampuan membaca siswa. Pengumpulan data dilakukan melalui observasi, wawancara mendalam dengan pustakawan dan guru, serta angket kepada siswa. Hasil penelitian menunjukkan bahwa perpustakaan sekolah memiliki peran signifikan dalam mendukung literasi membaca melalui berbagai program, seperti pembinaan minat baca, penyediaan koleksi buku relevan dan berkualitas, serta kegiatan literasi yang terintegrasi dengan kurikulum. Partisipasi aktif perpustakaan dalam kegiatan-kegiatan ini terbukti dapat meningkatkan keterlibatan siswa dalam kegiatan membaca. Selain itu, temuan penelitian ini menekankan pentingnya sinergi antara perpustakaan, guru, dan orang tua dalam membangun budaya membaca yang berkelanjutan. Studi ini menyarankan perpustakaan sekolah untuk terus memperkuat perannya dalam menciptakan lingkungan belajar yang kondusif dan mendukung pengembangan literasi siswa. Diharapkan bahwa langkah-langkah kolaboratif yang melibatkan berbagai pihak akan semakin meningkatkan efektivitas perpustakaan sebagai pusat literasi dan pembelajaran. Implikasi penelitian ini menegaskan pentingnya peran perpustakaan sekolah dalam meningkatkan literasi membaca siswa. Pihak sekolah perlu meningkatkan dukungan terhadap perpustakaan melalui pengadaan koleksi berkualitas dan program literasi yang berkelanjutan. Pelatihan pustakawan dan kolaborasi dengan guru serta orang tua harus dioptimalkan untuk menciptakan budaya membaca yang kuat. Kebijakan pendidikan yang mendorong pemanfaatan perpustakaan sebagai pusat literasi perlu diperkuat, sehingga perpustakaan dapat berfungsi maksimal sebagai agen perubahan dalam pengembangan literasi siswa.